The value of positron emission tomography computed tomography in predicting invasiveness of ground glass nodules: A protocol for systematic review and meta-analysis. Issue 41 (15th October 2021) - Xiao, Jitao; Li, Mengle; Du, Qun; Han, Hailin; Ge, Yinglin
Abstract: Background: The study was conducted to investigate the value of Positron emission tomography computed tomography (PET/CT) in predicting invasiveness of ground glass nodule (GGN) by the method of meta-analysis. Methods: Two researchers independently searched for published literature on PET/CT diagnosis of GGN as of November 30, 2020. After extracting the data, RevMan5.3 was used to evaluate the quality of the included literature. The Stata14 software was used to test the heterogeneity of the original study that met the inclusion criteria, to calculate the combined sensitivity, specificity, positive likelihood ratio and negative likelihood ratio, the prior probability and posttest probability. The summary receiver operator characteristic curve was drawn and the area under the curve was calculated. Using Deeks funnel plot to evaluate publication bias. Results: Five studies were finally included, including 298 GGN cases. The included studies had no obvious heterogeneity and publication bias. The combined sensitivity and specificity of PET/CT for predicting invasive adenocarcinoma presenting as GGN were 0.74 (95% confidence interval [CI]: 0.68–0.79), 0.82 (95% CI: 0.71–0.90), positive likelihood ratio and negative likelihood ratio were 4.1 (95% CI: 2.5–6.9), 0.32 (95% CI: 0.25–0.40), and the diagnostic odds ratio was 13 (95% CI: 7–26). The prior probability is 20%, the probability of GGN being invasive adenocarcinoma when PET/CT was negative was reduced to 7%, and the probability of GGN being invasive adenocarcinoma when PET/CT was positive was increased to 51%. The area under the curve of the summary receiver operator characteristic curve was 0.85. Conclusion: PET/CT has high diagnostic accuracy for invasive adenocarcinoma presenting as GGN.